Childhood Acute Lymphoblastic Leukemia: Progress Through Collaboration - Pui, Ching-Hon; Yang, Jun J; Hunger, Stephen P; Pieters, Rob; Schrappe, Martin; Biondi, Andrea; Vora, Ajay; Baruchel, André; Silverman, Lewis B; Schmiegelow, Kjeld; Escherich, Gabriele; Horibe, Keizo; et al. (Journal of clinical oncology, 2015)
To review the impact of collaborative studies on advances in the biology and treatment of acute lymphoblastic leukemia (ALL) in children and adolescents. A review of English literature on childhood ALL focusing on collaborative studies was performed. The resulting article was reviewed and revised by the committee chairs of the major ALL study groups. With long-term survival rates for ALL approaching 90% and the advent of high-resolution genome-wide analyses, several international study groups or consortia were established to conduct collaborative research to further improve outcome. As a result, treatment strategies have been improved for several subtypes of ALL, such as infant, MLL-rearranged, Philadelphia chromosome-positive, and Philadelphia chromosome-like ALL. Many recurrent genetic abnormalities that respond to tyrosine kinase inhibitors and multiple genetic determinants of drug resistance and toxicities have been identified to help develop targeted therapy. Several genetic polymorphisms have been recognized that show susceptibility to developing ALL and that help explain the racial/ethnic differences in the incidence of ALL. The information gained from collaborative studies has helped decipher the heterogeneity of ALL to help improve personalized treatment, which will further advance the current high cure rate and the quality of life for children and adolescents with ALL.